Shifting of Adjective Shift in The News “Immanuel Kant: Warum Seine Philosophie So Aktuell Ist” - Avisena, Satrio; Niartanaya, Bagas; Rusmana, Ahmad (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
This research examines the phenomenon of adjective shifts in the translation of news texts from German into Indonesian, focusing on the shifting of adjectives into different word classes in the target text. The case study is an article titled "Immanuel Kant: Warum seine Philosophie so aktuell ist" from DW.com, translated into "Filsafat Kant Makin Relevan di Tengah Konflik Geopolitik." The study aims to understand the dynamics of word class shifts and their implications for translation quality, particularly how adjectives in the source text affect the structure and meaning of the target text, and the subsequent impact on the accurate and precise delivery of information. The findings provide valuable insights into the linguistic adjustments necessary for effective cross-lingual communication and underscore the significance of word class considerations in news text translations.